PENGARUH PENGOLAHAN TANAH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TEMU IRENG (Curcuma aeroginosa) DI ANTARA KELAPA GENJAH KUNING NIAS - Rusli Rusli; Nana Heryana; Enny Randriani (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Effect of soil cultivation on growth and yield of curcuma (Curcuma aeroginosa) as intercrops between Nias yellow dwarf coconutThe growth and yield of intercrops between coconut beside affected by mikroclimate condition certainly affected by distribution of coconut roots. It can delay the developmant of intercrops root, more over if soil cultivation not right. This experiment to investigate the effect of soil cultivation technic on growth and yield of curcuma as intercrops under Dwarf coconut was used at Research Station for Intercrops Plantation, Pakuwon, Parungkuda, Sukabumi, West Java, beginning from October 2001 until August 2002. Randomized Complete Block Design with 4 treatments and 6 replications was used in this study. The Fourth of treatment are : (1). P0 (control / without cultivation), (2). P1 (cultivated totally), (3). P2 (cultivated of plant rows), and (4) P3 (by making seedling bed). Coconut variety that used is this experiment are Nias Yellow Dwarf (GKN) at 22 years old and planting distance of 7 x 7 m square system. Curcuma were planted about 1 m from coconut with 0,6 x 0,6 m spacing, effectively about 2400 m2. The parameter were observed ose : plant height, number of young plant, number of leaf, diameter and yield of highest main and branch rhizomes. From sample of 30 plants/plot. Result showed that soil cultivation technic had effect on growth and yield of curcuma. Totally soil cultivation technic gave a highest main and branch rhizomes, about 10,6 and 10,9 ton/ha respectively.